A nanoelectrode array for obtaining intracellular recordings from thousands of connected neurons - Abbott, Jeffrey (Nat Biomed Eng, 2019)
Current electrophysiological or optical techniques cannot reliably perform simultaneous intracellular recordings from more than a few tens of neurons. Here, we report a nanoelectrode array that can simultaneously obtain intracellular recordings from thousands of connected mammalian neurons in vitro. The array consists of 4,096 platinum-black electrodes with nanoscale roughness fabricated on top of a silicon chip that monolithically integrates 4,096 microscale amplifiers, configurable into pseudo-current-clamp mode (for concurrent current injection and voltage recording) or into pseudo-voltage-clamp mode (for concurrent voltage application and current recording). We used the array in pseudo-voltage-clamp mode to measure the effects of drugs on ion-channel currents. In pseudo-current-clamp mode, the array recorded intracellular action potentials and post-synaptic potentials from over thousands of neurons. In addition, we mapped over 300 excitatory and inhibitory synaptic connections from over 1,700 neurons that were recorded for 19 mins. This high-throughput intracellular-recording technology could benefit functional connectome mapping, electrophysiological screening, and other functional interrogations of neuronal networks.